Transformasi Limbah Kunyit secara Zero Waste: Inovasi Gummy Herbal dan Pupuk Organik Cair dalam Pemberdayaan Kelompok Tani Perempuan 'Tani Lestari' Desa Kunden, Sukoharjo - Elvi Wulandari; Andira Luthfi Cahyani; Elisabeth Elvira Vianney; Sherlinda Fadlillah,; Syavira Annastasya; Teuku Radhi Fahlani; Melati Dewi Pertiwi; Nur Hanggara Putra; Sitti Aisyah Az'Zahra; Indah Nurhidayati (Lembaga Pengembangan Kinerja Dosen, 2025)
Turmeric is a spice commodity that has high economic market potential. However, the utilization of turmeric, especially in Kunden Village, Sukoharjo Regency is still limited in terms of processing innovation, and creates organic waste that has not been optimally utilized, namely turmeric leaves. The Village Development Program, carried out a zero waste-based transformation through the manufacture of gummy spices from rhizomes and liquid organic fertilizer from turmeric leaf waste. This activity is with the farmer women's group of Tani Lestari, with stages of socialization, training, and practice. The results of this program show that the farmer women's group of Tani Lestari members are able to understand product processing innovations in the form of turmeric gummy and optimize turmeric leaf waste into liquid organic fertilizer. Gummy turmeric is a functional food product that is good for health, while liquid organic fertilizer is an alternative to reducing organic waste from turmeric leaves to support sustainable agriculture. The provision of e-modules strengthens the sustainability of the program even after the activity has ended. Zero waste-based innovation not only encourages community participation, especially farmer women's group in village development based on local resources, but also creates a community that is adaptive to progress.